Synthetic Cast Material Versus Plaster of Paris for the Treatment of Idiopathic Clubfoot by the Ponseti Protocol: A Comparative Analysis of 136 Feet - Monforte, Sergio; Alberghina, Flavia; Paonessa, Matteo; Canavese, Federico; Andreacchio, Antonio (Journal of pediatric orthopaedics, 2021)
Synthetic casting materials have been used as alternatives to plaster of Paris (POP) in the treatment of clubfoot using the Ponseti method. The aim of this study was to evaluate the clinical outcome of children with idiopathic clubfoot managed by the Ponseti method using POP versus semirigid fiberglass (SRF). Medical records were retrospectively reviewed for all newborns with idiopathic clubfoot who underwent manipulation and casting by the Ponseti technique between January 2013 and December 2016 at 2 different institutions. In all, 136 consecutive clubfeet were included, of which 68 underwent casting with POP (Group A), and 68 were casted using SRF (Group B). Statistical analysis was performed using the Fisher exact test for categorical variables, and the unpaired t test for quantitative parameters. Mean age at time of first cast was 10 days (range, 3 to 21 d). Mean Pirani score at start of treatment was 4.6 and 4.5 in Groups A and B, respectively. Mean number of casts for each patient in Group A was 5.2 against 4.2 in patients in Group B. Mean follow-up was 63.8 months (range, 42 to 88 mo). In each group, 4 cases of relapse were reported (2.9%). No complications related to cast phase or brace phase were recorded. Shorter duration of cast treatment was recorded in Group B. Despite its higher cost and slightly lower moldability, the use of SRF in experienced hands showed comparable results in idiopathic clubfeet treated by the Ponseti technique. Level III.